Hepatoid adenocarcinoma of the duodenal papilla with hepatic metastases: A case report and literature review - Han, Lu; Ding, Naiqing; Li, Li; Wei, Xiao; Hu, Jing; Liu, Baorui; Qian, Xiaoping (Frontiers in Oncology, 2022)
Hepatoid adenocarcinoma of the duodenum is a rare, special type of adenocarcinoma, featured by hepatocyte components in primary adenocarcinoma of the duodenum. It has the characteristics of high malignancy, invasiveness, rapid progress and poor prognosis. An abnormal elevation of serum alpha-fetoprotein (AFP) may occur in most cases. And the diagnosis is mainly based on pathological morphology. Here we reported a case of hepatic adenocarcinoma of the duodenum. The middle-aged female patient had an ampulla mass at diagnosis and received radical pancreaticoduodenectomy. The postoperative pathology was stage IIIA duodenal adenocarcinoma. While one month after surgery, she had multiple intrahepatic metastases and retroperitoneal lymph node metastasis, the AFP level was 300 ng/ml at that time. As she refused target therapy, 2 cycles of XELOX chemotherapy were performed. However, the AFP elevated from 300 ng/ml to 1931.90 ng/ml and the disease progressed rapidly. Immunohistochemistry (IHC) of tissue samples from pre-surgical EUS-FNA, surgery and liver biopsy showed positive AFP staining, combining the abnormal elevation of serum AFP and microscopic pathological morphology, this case is diagnosed as hepatoid adenocarcinoma of the duodenum with liver metastasis.The physical condition of this patient was too poor to receive follow-up treatment. And she died of the rapid disease progression with an overall survival time of 161 days. Considering that in most patients with hepatoid adenocarcinoma, the abnormal elevation of serum AFP occurs preoperatively and returns to normal postoperatively rather than normal before surgery and increased after surgery, the primary lesion is located in stomach rather than intestine, and the patients are more often elder men rather than middle-aged females, this case is rare particularly.Therefore, reporting this case with complete case data may be helpful to further study, so as to improve the understanding of this special type of malignant tumor.